Exploring media framing of abortion content on Kenyan television: a qualitative study protocol - Catherine Kafu; Dina Ligaga; Juddy Wachira (BMC, 2021)
Abstract Background Media framing of abortion messages is an emerging field of research. However, little is known about how the news media frames abortion messages aimed at influencing adolescents' reproductive health choices. This study therefore seeks to investigate the framing of abortion in TV news items on three leading Kenyan TV outlets over a period of 3 years, understand Kenyan journalists' perceptions and experiences with abortion coverage, and to examine adolescents' perceptions and experiences with abortion coverage on Kenyan televised news media. Methods This qualitative study which will be conducted in two sites-Nairobi and Uasin Gishu counties-in Kenya will purposively sample abortion news items from three leading media outlets aired between January 2016 to December 2019, for content analysis. Additionally, 12 journalists (9 reporters, 3 news editors) will be purposively sampled for Key Informant Interviews (KIIs) on journalist framing of abortion messages. Finally, convenience sampling will be used to select approximately 48 university-going adolescents for four Focus Group Discussions (FGDs)-2 female, 2 male- aimed at examining adolescents' perceptions and experiences with abortion coverage in the broadcast news media. The KIIs and FGDs will be audio-recorded, transcribed and translated. These data will be analyzed thematically. Discussion This study moves beyond interrogating only media items to further exploring framing from the perspectives of media consumers and investigations in the process behind production of abortion messages. The study interrogates abortion messages aimed at younger demographics such as adolescents as well as the gendered differences of the effects of these abortion messages, an area barely explored. The study findings will be informative to those who wish to develop media that could be used to promote safe abortion as well as advocate for sexual reproductive health rights, especially among adolescents.